Testosterone/cortisol ratio: gender effect and prediction of podium results in beach sprint master rowers - Ficarra, Giovanni; Rottura, Michelangelo; Mannucci, Carmen; Caccamo, Daniela; Bitto, Alessandra; Trimarchi, Fabio; Di Mauro, Debora (Frontiers in Sports and Active Living, 2024)
The purpose of this study is to address the lack of data on the stress and motivation response in master athletes during competitions, as athletic performance in this age group can be significantly impacted by stress rather than appropriate training.Coastal rowing beach sprint master athletes aged 43 to 57 years were examined to assess the saliva levels of stress biomarkers, cortisol, and testosterone. Specifically, samples were collected at awakening, before and after boat race.Results: Mean values of cortisol remained unchanged from awakening and raised at the end of the competition; while testosterone levels increased before the race suggesting an aggressive/competitive behavior. Cortisol levels were significantly higher when comparing prerace with end of the race (p=0.001); and early morning with end of the race (p=0.006) levels.No gender effect was observed in this case. Testosterone values did not demonstrate significance when compared between time points, not even when stratifying by gender.Considering the 24 athletes, a higher testosterone/cortisol ratio was correlated with a worse podium position (B= 3.705; p=0.009). When stratified by gender, the T/C ratio demonstrated an association with a worse outcome of the race only in female rowers (B= 4.012; p=0.022).Male athletes demonstrated no significant correlation between hormone ratio and race results (B= 3.288; p=0.292).As emerged from this study the amateur rowers that approach competitive sport during adulthood may have problems in coping with the race-related stress and thus the outcome of their performance might be affected, as it happens in adolescents.